Pseudohypertension-Like Presentation: An Exceptionally Rare Presentation in an Athletic Female Patient with Morphea - Ahmed Al-Imam (Case Reports in Dermatological Medicine)
Introduction. Pseudohypertension is a condition which mainly occurs due to thickening-calcification of tunica intima of the arterial wall, leading to a faulty measurement of the intra-arterial blood pressure. To the best of our knowledge, this is the first case report in literature, of a pseudohypertension-like presentation in association with Morphea en plaque. Case Presentation. This is a rare presentation of a young athletic female and a professional tennis player, with pseudohypertension-like presentation. The patient had a traumatic injury to the right elbow joint; the injury occurred during a professional tennis match. The injury was managed by immobilization, physiotherapy, and Low-Level Laser Therapy. Soon after that, the patient had a circumscribed sclerotic ivory plaque affecting the skin of the right cubital fossa. The histopathology analysis, together with the serological-hematological tests and the clinical picture, along with positive Osler’s signs, leads to the conclusive diagnosis of Morphea en plaque. The peculiar anatomic localization of the plaque anterior to the brachial artery leads to faulty blood pressure measurement as recorded by mercurial sphygmomanometer. Conclusion. This unique presentation of Morphea en plaque carries an important message in relation to the basic medical practice and in relation to the accurate measurement of the vital signs.